TOT on digital advisory services to smallholder farmers - Tesfaye, Kindie (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Workshop presentation. Addis Ababa, Ethiopia. May 3rd, 2022. LERSHA Platform, GAS Office.